Epistemic violence: an analytical tool for theorising the interconnections of violences - Pérez, Moira (Interconnecting the violences of men, 2025)
The chapter explores epistemic violence both as a phenomenon and as an analytical lens that can bring a more nuanced understanding of violence at large and of its relationship with masculinities. In the first section, we characterise three forms of epistemic violence and explore how they supply the epistemic dividend of hegemonic and dominating masculinities: the unequal distribution of epistemic authority, testimonial injustice, and unequal access to epistemic resources. The second section displays some analytical insights opened by four features of epistemic violence and considers their contribution to theoretical and practical approaches to violence and masculinities: its directionality, its temporality, its relation to intersected identities, and its interconnectedness with other forms of violence. We conclude that epistemic violence should be regarded as at once a field of violence, a facilitator for other forms of violence, and an obstacle to understanding, preventing, and repairing violence at large. Finally, we expose how epistemic violence can be reproduced in academic research and suggest some practices to counter it.